Melting And Densification Of Electrode Paste Briquettes In Søderberg Electrodes - B. Larsen; J. P. M. Amaro; S. Z. Nascimento; K. Fidje; H. Gran (The Southern African Institute of Mining and Metallurgy, 2004)
Safe and good operation of Søderberg electrodes is dependent upon high quality electrode paste coupled with correct electrode operating procedures. Good electrode performance depends further on proper melting and densification of the electrode paste. The melted paste should form a dense and viscous layer that prevents gasses from the baking process to move upwards. Both paste cylinders/blocks and briquettes can be used, but the procedures may differ between the various types of paste products. For briquette columns the formation of the important viscous layer is obtained through melting and densification of the briquettes. By basic rheological studies of electrode paste and by laboratory tests of briquette beds at isothermal conditions we have achieved a better understanding of the melting process. The effects of temperature gradients, pressure and friction between the briquettes and the electrode casing have also been evaluated qualitatively in pilot scale experiment and in industrial scale tests. The paper shows that melting and densification starts at a considerable lower temperature than the pitch softening temperature. It is concluded that the formation of a briquette electrode column depends on parameters as temperature, briquette column pressure and the friction. Operating conditions influencing the above parameters should be defined and established for each specific furnace operation. Such factors are e.g., charging and slipping procedures, column heating and electrical conditions.